If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + ln(x + 3) = 0 Reorder the terms: 2 + ln(3 + x) = 0 2 + (3 * ln + x * ln) = 0 2 + (3ln + lnx) = 0 Solving 2 + 3ln + lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 3ln + -2 + lnx = 0 + -2 Reorder the terms: 2 + -2 + 3ln + lnx = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3ln + lnx = 0 + -2 3ln + lnx = 0 + -2 Combine like terms: 0 + -2 = -2 3ln + lnx = -2 Reorder the terms: 2 + 3ln + lnx = -2 + 2 Combine like terms: -2 + 2 = 0 2 + 3ln + lnx = 0 The solution to this equation could not be determined.
| -4=4-8x | | y-7=-5(x+3) | | 4-4=6-6 | | x/0.4-2x-1.2=0 | | 6.4=-.4r | | 2+1n(x+3)=0 | | 4x+10=1080 | | (4x+12)+(x+6)+x= | | 172n+45=131 | | 1.2+2w=0.2+1.3w | | (x-5)=95 | | 15x+4=9x+28 | | 3ax-bx=bx^2-ax | | -.05x^2+2.5x=0 | | 15.8/xr.7 | | 3ax-bx=bx^2-ab | | 4(x-2)+64=-4 | | r-28=9 | | 27.28x+0.20=32.28 | | 56=3x+4y | | -11z=-99 | | 5y-(8y+10)=7-(13y-4) | | 4(2x+2)=8x | | 6y+12y=30 | | -2m+1=-7 | | 0.20x-27.28=32.28 | | 2(x-1)-4(x+1)=0 | | x+2+x-8+x+7+x-3+x+6+x-4= | | 2(x-1)-4(x+1)=1 | | 8+u=14 | | Ln(x^2-4)-ln(x-2)=-ln(x-2) | | 0.20x+27.28=32.28 |